Integrated manufacturing of co-cured skin-stringer composite structures - Chew, Aaron Wai Yean (2018)
As the use of Carbon Fibre Reinforced Polymer (CFRP) have increasingly become the primary material for structures in the aerospace industry, the methodology of manufacturing structures from this composite material has gained interest, with a focus on reducing resource, manpower and time cost associated with its complexity. One such method of manufacturing is known as co-curing, which involves many smaller parts curing together to form a larger structure. In this study, the methods of fabrication of co-cured skin-stringer composite structures are examined and investigated experimentally through the fabrication of a box shaped skin-stringer panel with one stringer. Fabrication methodology is examined in terms of three parameters, namely, the manner of tooling or mold used in laminate layup, the choice of the inner mold as cavity, and the equipment and method of curing the prepared layup. A key development in this study was the adoption of a new curing method known as the inflatable tubing molding technique. Developed from the bladder molding technique, the inflatable tubing molding’s uses a disposable nylon tubing sheet and works based on the pressure differential between the interior of the tubing and the exterior when curing, which provides strong support to the composite layup as it cures. This study also tested the specimens produced by the new method to examine the behaviour under loading until failure through a buckling and compression test. The buckling behaviour was found to consist of the following characteristic stages: I) The initiation of buckling in the skin; II) The development of the buckling mode shape; III) The initiation of buckling in the stringer and IV) The explosive collapse of the specimen. This visual observation is co-related to the load-displacement and strain-load data obtained from the tests, which agrees with the observations. The compression test which investigated the skin-stringer bond identified qualitatively that the bond of the co-cured specimen was able to withstand the shear force applied in the test between the skin and stringer without delaminating, which indicates the integrity of the bond formed by the co-cured method. A drum peel test is recommended for future work to quantitatively study this bond.